Effect Of Motivation And Organizational Commitment On Employee Performance At The Jakarta Provincial Inspectorate - Hakim, Azis (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of motivation and organizational commitment on employee performance in the Jakarta Provincial Inspectorate. The research sample of 65 respondents with a random sampling technique. Data analysis uses regression analysis. The results showed that organizational motivation and commitment had a positive and significant ef ect on employee performance.